Քննական ակնարկ Արցախի բանաստեղծների ստեղծագործությունների լեզվական արվեստի - Ղազարյան, Հասմիկ
В статье из множества методов и приемов искусства художественного слова арцахских поэтов кратко проанализированы те факты лексики и грамматики, которые придают особый колорит их произведениям и обусловливают народность и метричностъ их поэзии. In the article of the great nymber of methods and ways of Artsakh poets’ word art, are briefly analysed the facts of vocabulary and grammar that give a particular colouring to their poetry and simulate the nationality and the metric of their poesy.
Keywords: Հայոց լեզու; Գրականություն